On Best Proximity Points of Generalized Almost-F-Contraction Mappings - Mahdi Salamatbakhsh; Robab Hamlbarani Haghi (Journal of the Indonesian Mathematical Society, 2019)
We provide some results about best proximity points of generalized almost-$F$-contraction mappings in metric spaces which generalize and extend recent  fixed point theorems. Also, we give an example to illustrate  our main result.